2021
DOI: 10.1016/j.mcpro.2021.100121
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Landscape of Exosomes Reveals the Functional Contributions of CD151 in Triple-Negative Breast Cancer

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
48
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 45 publications
2
48
0
1
Order By: Relevance
“…In this process, the ASPH-Notch axis helped to prepare MMPs/ADAMs for exosomes synthesis/release, which was conducive to potentiate multifaceted metastasis. Sipeng Li et al (2021) identified that the expression level of CD151 in TNBC-derived serum exosomes was markedly higher than that in healthy subject exosomes. Using quantitative proteomics methods, they found that exosome CD151 promoted ribosomal protein secretion through exosomes and restrained exosome complement protein secretion.…”
Section: Extracellular Vesicles In Triple-negative Breast Cancer Meta...mentioning
confidence: 98%
“…In this process, the ASPH-Notch axis helped to prepare MMPs/ADAMs for exosomes synthesis/release, which was conducive to potentiate multifaceted metastasis. Sipeng Li et al (2021) identified that the expression level of CD151 in TNBC-derived serum exosomes was markedly higher than that in healthy subject exosomes. Using quantitative proteomics methods, they found that exosome CD151 promoted ribosomal protein secretion through exosomes and restrained exosome complement protein secretion.…”
Section: Extracellular Vesicles In Triple-negative Breast Cancer Meta...mentioning
confidence: 98%
“…For example, UCHL1 (ubiquitin carboxyl-terminal hydrolase isozyme L1) harboured in TNBC-TEVs has been proposed as a biomarker for TNBC [ 121 ]. It is also applicable to use surface membrane proteins (e.g., CD151) present on TNBC-TEVs as biomarkers for diagnosing TNBC [ 122 ]. Additional examples of potential protein biomarkers for TNBC-TEVs include the epidermal growth factor receptor (EGFR) and survivin [ 123 , 124 , 127 ].…”
Section: Using Evs As Diagnostic/prognostic Biomarkers For Tnbcmentioning
confidence: 99%
“…Using this Azo-enabled method, exosome extraction and sample preparation require only ~2.5 h, compared to traditional methods employing overnight digestion and/or lengthy prefractionation that may take 16 to 24 h total. [15][16][17][18][19][20] The subsequent LC-TIMS-MS/MS analysis enhanced by PASEF drastically increases sensitivity without increasing analysis time, obviating the need for multidimensional LC or prefractionation, and increasing the total number of proteins identified in the extraction. 24,25 We have applied this method to analyze mammary fibroblast-derived exosomes.…”
mentioning
confidence: 99%
“…7 Mass spectrometry (MS)-based proteomics is one of the most promising techniques for the global identification and quantification of proteins, [8][9][10] and has recently been employed to characterize exosomal protein cargoes. 1,7,[11][12][13][14][15][16][17][18][19][20] Typically, bottom-up proteomic methods are used in these MS-based analyses of EVs, but the sample preparation typically involves the use of MSincompatible detergents for protein extraction, overnight and/or multiple enzymatic digestions, and lengthy multidimensional chromatographic separations. [15][16][17][18][19][20] The elongated experimental time and complexity required to improve exosomal proteome coverage in these previously established methods significantly reduce the throughput and reproducibility, limiting the potential of MSbased proteomic analysis of exosomes in translational and clinical applications.…”
mentioning
confidence: 99%